Retinoic Acid Regulates Endothelial β-catenin Expression and Pericyte Numbers in the Developing Brain Vasculature - Bonney, Stephanie; Dennison, Brenna J. C.; Wendlandt, Megan; Siegenthaler, Julie A. (Frontiers in Cellular Neuroscience, 2018)
The acquisition of brain vascular properties, like tight junctions and pericytes, to form the blood-brain barrier (BBB) is crucial for a properly functioning central nervous system (CNS). Endothelial WNT signaling is a known driver of brain vascular development and BBB properties however it is unclear how endothelial WNT signaling is regulated. We recently showed that mouse embryos with disruptions in endothelial retinoic acid (RA) signaling have ectopic WNT signaling in the brain vasculature. Using immunohistochemistical analysis, we show that increased vascular WNT signaling in RA mutants (Pdgfbicre; dnRAR403-flox and Rdh10 mutants) is associated with elevated expression of the WNT transcriptional effector, β-catenin, in the brain endothelium. In vitro immunocytochemistry and proximity ligation studies in brain endothelial cells reveal that RA, through its receptor RARα, regulates β-catenin expression in brain endothelial cells via transcriptional suppression and phosphorylation events that targets β-catenin for proteasomal degradation, the latter dependent on PKCαWe find that one function of RA in regulating vascular WNT signaling is to modulate the pericyte numbers in the developing brain vasculature. RA-mediated regulation of vascular WNT signaling could be needed to prevent over-recruitment of pericytes that might impair endothelial-pericyte interactions crucial for vascular stability.